2018
DOI: 10.1055/a-0579-6494
|View full text |Cite
|
Sign up to set email alerts
|

New report preparation system for endoscopic procedures using speech recognition technology

Abstract: Background and study aims  We developed a new reporting system based on structured data entry, which selectively extracts only endoscopic findings from endoscopists’ oral statements and automatically inputs them into appropriate columns in real time during endoscopic procedures. Methods  We compared the time for endoscopic procedures and report preparation (ER time) by using an esophagogastroduodenoscopy simulator in three groups: one preparing reports using a mouse after endoscopic procedures (CE group); a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Our previous study with the SR software program and an upper gastrointestinal endoscopy simulator demonstrated a correct recognition rate of 98.4% ( 10 ). The role of SR software programs in other disciplines has been examined, and the highest correct recognition rate of 96% was documented in radiologic reports ( 1 - 4 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study with the SR software program and an upper gastrointestinal endoscopy simulator demonstrated a correct recognition rate of 98.4% ( 10 ). The role of SR software programs in other disciplines has been examined, and the highest correct recognition rate of 96% was documented in radiologic reports ( 1 - 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…We jointly developed the original Japanese SR system for reporting endoscopic findings equipped with VoiceRex Ⓡ (Nippon Telegraph and Telephone Corporation, Tokyo, Japan) in collaboration with Fujifilm Medical IT Solutions, NTT TechnoCross Corporation, and Nippon Telegraph and Telephone Corporation. The original SR system was used in a preliminary study with an endoscopic simulator ( 10 ). In the present study, we upgraded the VoiceRex Ⓡ system by introducing the latest technology ( 11 , 12 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The preliminary assessment of construct validity was based on the median time needed to complete the tasks. This concept has been used in previous pilot studies [11].…”
Section: Outcome Variables and Data Collectionmentioning
confidence: 99%